Severe tenosynovitis with rapidly fluctuating power Doppler activity, a clue for the diagnosis of Blau syndrome: a case report - Pastore, Serena; Carraro, Carolina; De Martino, Eleonora; Pin, Alessia; Bruno, Irene; Zanotta, Nunzia; Valencic, Erica; Tommasini, Alberto; Taddio, Andrea (Frontiers in Pediatrics, 2025)
BackgroundBlau Syndrome is a rare monogenic disorder characterized by granulomatous polyarthritis, dermatitis, and uveitis. The diagnosis can be challenging as symptoms may not always align with the classic triad.Case descriptionAn 8-year-old girl presented with fluctuant swellings in the wrists and ankles, strength reduction and stiffness. Blood tests showed lymphopenia, elevated inflammation markers and positivity of anti-nuclear antibodies. Ultrasound revealed severe tenosynovitis with no power Doppler signal. After fifteen days, she developed fever and widespread joint pain. Laboratory tests detected a marked worsening of inflammatory indices. Musculoskeletal ultrasound showed severe tenosynovitis with a prominent power Doppler signal. A targeted genetic investigation identified a de novo pathogenic variant in the NOD2 gene, confirming the diagnosis of Blau Syndrome. The patient underwent brief treatment with corticosteroids and long-term therapy with methotrexate and adalimumab, achieving good clinical improvement.ConclusionThe diagnosis was suspected based on severe tenosynovitis of wrists and ankles with power doppler signal fluctuation, despite the absence of other typical Blau Syndrome symptoms. High cytokines levels were observed, which normalized after treatment. Transcriptomic analysis revealed an increased expression of genes related to cellular stress and induction of the TNF pathway.